Renal Function in Children on Long Term Home Parenteral Nutrition - Messova, Assylzhan; Dziubak, Robert; Köglmeier, Jutta (Frontiers in Pediatrics, 2019)
.Objectives: To assess renal function in paediatric intestinal failure (IF) patients on long term home parenteral nutrition (HPN). Methods: Children who received HPN for a minimum of three years between 2007 and 2017 were identified from the IF clinic of a large tertiary referral centre. Estimated glomerular filtration rate (eGFR) was calculated using the Schwartz formula at discharge on HPN, after 6 months, 1, 2, and 3 years. Results: Twenty five patients (40% male) fulfilled the inclusion criteria. The indications for HPN were due to an underlying motility disorder in 56% (14/25), enteropathy in 24% (6/25) and short bowel syndrome in 20% (5/25). At the start of HPN 80 % (20/25) had a normal eGFR. Four children (17%) had an abnormal eGFR. In the group of patients with normal eGFR at the start of HPN 30% (6/20) had at least one episode of decreased eGFR in the following three years, however there was no significant decline in eGFR at the end of the 3 year study period. Overall there was no statistically significant deterioration of eGFR in the study population (p = 0.7898). Conclusion: In our cohort of children on long term HPN no significant decline of eGFR could be demonstrated within three years of starting PN.